Effect of negative pressure therapy on repair of soft tissues of the lower extremities in patients with neuropathic and neuroischaemic forms of diabetic foot syndrome - Ekaterina Leonidovna Zaytseva; Ludmila Petrovna Doronina; Roman Vakhtangovich Molchkov; Iya Alexandrovna Voronkova; Valeriy Afanasievich Mitish; Alla Yur'evna Tokmakova (Сахарный диабет)
Aim. To evaluate the efficiency of topical negative pressure wound therapy (NPWT) compared with standard therapy for the regeneration of the soft tissues of the lower extremities in patients with diabetic foot syndrome. Materials and Methods. The effects of negative pressure therapy on the clinical (size, tissue oxygenation), histological (light microscopy) and immunohistochemical (CD68, MMP-9, TIMP-1) aspects of repair of the soft tissue of the lower extremities in patients with diabetes mellitus were compared with those of standard treatment. Thirty-one patients with diabetic foot ulcers were included in the study from the moment of debridement until the plastic closure of the wound. During the perioperative period, 13 patients received NPWT (-90 to -120 mmHg) and 18 patients received standard therapy. Results. A reduction of the wound area (26.6%?17.2%) and the depth of the defects (40.5%?25.6%) were achieved with negative pressure therapy compared with baseline data. In the control group, the corresponding values were 25.3%?19.4% and 21.8%?21.6%, respectively. The results of transcutaneous oximetry showed a greater increase in the level of local hemodynamics in the study group (p